Applying the U.S. Model of Social Work Education Curriculum to Libyan Education (Global Journal of Human-Social Science, 2021)
The Libyan government urgently needs a professional social workers' mission to help decrease social problems that have emerged and been aggravated due to civil war and political conflicts. However, the present social work community in Libya cannot mitigate social problems or simplify social services effectively to meet people's needs. Thus, teaching and learning methodologies need to be developed inside and outside educational institutions so that the challenges presently facing Libyan society can be overcome. The purpose of this paper is to suggest adopting an American social work curriculum experience in Libyan social work education according to Libyan ideology. The researcher depicts nine social work competencies (e.g., knowledge, professional values, skills, and professional processes and practices), as well as a set of behaviors that reflect social workers' competencies that relate to the social work curriculum applied in colleges in the United States. The author's goal is to encourage Libyan social work professionals to take advantage of this knowledge and these experiences to develop the Libyan social work education curriculum. This could ensure that graduates of social work programs are qualified to help people deal with social problems when they enter the workforce.
Keywords: libya; government; mission; ideology; american; social work; curriculum; education; teaching